Bersaldegenin-1, 3, 5-orthoacetate induces caspase-independent cell death, DNA damage and cell cycle arrest in human cervical cancer HeLa cells. (1st January 2021) - Stefanowicz-Hajduk, Justyna; Gucwa, Magdalena; Moniuszko-Szajwaj, Barbara; Stochmal, Anna; Kawiak, Anna; Ochocka, J. Renata
Abstract: Context: Bufadienolide compounds occur in many plants and animal species and have strong cardiac and anti-inflammatory properties. The compounds have been recently investigated for cytotoxic and antitumor activity. Objective: The cytotoxic effect of bersaldegenin-1, 3, 5-orthoacetate – a bufadienolide steroid occuring in plants from Kalanchoe genus (Crassulaceae), was evaluated with cervical cancer HeLa cells in vitro . Materials and methods: The cytotoxic activity of the compound (at 0.1–20.0 μg/mL) on the cells was determined by Real-Time Cell Analysis (RTCA) system for 24 h. The estimation of cell cycle arrest, reactive oxygen species (ROS) production, reduction of mitochondrial membrane potential (MMP), and caspases-3/7/9 activity in the HeLa cells treated with the compound was done by flow cytometry and luminometric technique. DNA damage in the cells was estimated by immunofluorescence staining and the comet assay with etoposide as a positive control. Results: The compound had strong effect on the cells (IC50 = 0.55 μg/mL) by the suppression of HeLa cells proliferation in G2/M phase of cell cycle and induction of cell death through double-stranded DNA damage and reactive oxygen species overproduction. Furthermore, we did not observe an increase in the activity of caspase-3/7/9 in the treated cells as well as a decrease in cellular mitochondrial membrane potential. Gene expression analysis revealed the overexpression of NF-Kappa-B inhibitors genes (>2-fold higher than control) in the treated cells. Conclusions: Bersaldegenin-1, 3, 5-orthoacetate induces cell cycle arrest and caspase-independent cell death through double-stranded DNA damage. These results are an important step in further studies on cell death signalling pathways induced by bufadienolides.